Pemanfaatan Limbah Cangkang Kerang Kijing (Pilsbryoconcha exilis) dalam Meningkatkan Perekonomian Warga Desa Bulupayung-Kesugihan, Cilacap, Jawa Tengah - Rachmi Ridho; Mika Tri Kumala Swandari; Elisa Issusilaningtyas (Institut Pertanian Bogor, 2017)
The Cilacap District area in Central Java Province has a high biodiversity in sea water and fresh water ecosystems due to surrounded by the sea and fresh water environments. The main focus in the Ipteks activities for the peoples (IbM) is to study the potency of Serayu River as an ecosystem of fresh water shell Pilsbryoconcha exilis (kerang kijing). At present, this water fresh shell is harvested only for the meat, while the eggshell is become a waste and not yet utilize for other purposes. To utilize the eggshell which is rich of calcium carbonate to be an economic value, the right method of waste management is needed. The eggshell will be developed as a source of raw materials for cosmetic purposes. The huge amount of eggshell in the Village of Bulupayung-Kesugihan, Cilacap is not yet utilize. The goal of the present study through an IbM scheme is to establish and develop a village community entrepreneur on the waste management of P. exilis eggshell in the community. The IbM activities were consisted of IbM programme socialization and information collection, establishment of community entrepreneur, training, marketing network establishment and development, marketing of IbM product, and economic calculation of the eggshell powder. The present IbM activities that focused on the utilization of P. exilis eggshell waste management has successfully enhanced the economic added value of the eggshell and gave a positive impact by increasing the income of the local community entrepreneur members and triggered the economic enhancement of the local community.